Composite lithium-supplementing negative electrode material as well as preparation method and application thereof
By using functional materials of core-shell structure to coat silicon negative electrode particles, the poor circulation performance and safety hazards caused by volume changes in silicon-based materials in lithium-ion batteries are solved, and better battery circulation and safety performance are achieved.
Patent Information
- Application Number
- CN202411631231.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-04
AI Technical Summary
Silicon-based materials will undergo huge volume changes during the process of lithium ions embedded and disengagement, resulting in poor battery circulation performance. The existing lithium supplementation method has problems such as safety hazards and high environmental sensitivity.
Functional materials with core-shell structure are used to coat silicon negative electrode particles, including lithium supplement cores and polyurethane material coating, to inhibit the expansion of silicon negative electrode particles, and to achieve rapid lithium supplementation and blocking during charging and discharging, improving battery circulation and safety performance.
It effectively suppresses the expansion of silicon negative electrode particles, improves the cycle performance and safety performance of the battery, and reduces the sensitivity to ambient temperature and humidity.
Smart Images

Figure CN119560524A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a composite lithium-supplementing negative electrode material and a preparation method and application thereof. Background Art
[0002] Silicon-based materials have a very high theoretical specific capacity (4200mAh / g), and their application in lithium battery negative electrodes will help improve the energy density of batteries. However, silicon-based materials undergo huge volume changes during the process of lithium ion insertion and extraction, which will cause silicon particles to break and pulverize during battery cycling, and fall off the current collector. In addition, the huge volume changes will cause the SEI film on the surface of silicon particles to break and regenerate continuously, consuming a large amount of lithium ions in the electrolyte, ultimately leading to rapid battery capacity decay and poor cycle performance, which severely limits the commercial application of silicon-based materials.
[0003] In order to further improve the cycle performance of materials such as silicon negative electrodes, the existing technology can significantly reduce the volume expansion of materials during cycling through methods such as nano-processing and surface coating, thereby improving the cycle performance of the battery. In addition, the existing technology also discloses pre-lithiation treatment of materials, and the use of lithium replenishers to replenish lithium to the positive and negative electrodes, so as to make up for the irreversible capacity loss of the battery during the first cycle of charging and discharging and the cycle process, and can also effectively improve the cycle life and storage performance of lithium batteries. However, the lithium replenishment method has extremely high requirements for environmental temperature and humidity, and highly active lithium metal or lithium replenishers are very easy to react with moisture in the air and carbon dioxide, etc., resulting in safety hazards to the battery and failure of the lithium replenisher.
[0004] Therefore, it is urgent to develop a new technical means to solve the above technical problems. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a composite lithium supplement negative electrode material, which uses a functional material with a core-shell structure to coat silicon negative electrode particles, which can inhibit the expansion of silicon negative electrode particles and improve the battery cycle performance to a certain extent. In addition, the functional material includes a lithium supplement agent core and a polyurethane material coating layer, which can play a lithium supplement effect; at the same time, during the battery charging process, lithium ions escape from the positive electrode and embed into the negative electrode, causing the negative electrode material to expand, and the particle expansion and extrusion will cause the polyurethane material in the functional material coating layer to rupture, releasing part of the lithium supplement agent, and realizing rapid lithium supplementation. When the battery is discharged, lithium ions escape from the negative electrode and embed into the positive electrode, and the negative electrode material shrinks. The repair function of polyurethane can be used to block the lithium supplement agent to avoid battery side reactions, thereby simultaneously improving the battery cycle performance and safety performance.
[0006] In order to achieve the above technical objectives, the technical solution of the present invention is as follows:
[0007] The present invention provides a composite lithium-supplementing negative electrode material, comprising silicon negative electrode particles and a coating layer arranged on the surface of the silicon negative electrode particles, wherein the coating layer comprises a functional material; the functional material is a core-shell structure, wherein the core comprises a lithium-supplementing agent, and the shell comprises a polyurethane material.
[0008] In one embodiment of the present invention, the silicon negative electrode particles include at least one of nano-silicon, silicon-oxygen material and silicon-carbon material.
[0009] In one embodiment of the present invention, the lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2.
[0010] In one embodiment of the present invention, the particle size D50 of the silicon negative electrode particles is 5 μm to 15 μm.
[0011] In one embodiment of the present invention, the coating layer has a thickness of 1 μm to 5 μm.
[0012] In one embodiment of the present invention, the particle size D50 of the lithium supplement agent is 0.2 μm to 0.8 μm.
[0013] In one embodiment of the present invention, the shell thickness of the polyurethane material is 2nm-50nm.
[0014] In one embodiment of the present invention, the mass ratio of the silicon negative electrode particles to the functional material is (85-95):(5-15).
[0015] In one embodiment of the present invention, the polyurethane material accounts for 0.5wt% to 5wt% of the coating layer.
[0016] In one embodiment of the present invention, the coating layer further comprises carbon material.
[0017] In one embodiment of the present invention, the carbon material accounts for 20 wt% to 40 wt% of the coating layer.
[0018] In one embodiment of the present invention, the carbon material includes one or more of graphene, carbon nanotubes and conductive carbon black.
[0019] The present invention also provides a method for preparing a composite silicon-carbon negative electrode sheet, comprising the following steps:
[0020] Mixing the lithium supplement agent and the polyurethane solution to obtain a mixed solution;
[0021] Drying the mixed solution to obtain a functional material;
[0022] The functional material and silicon negative electrode particles are ball-milled to obtain a composite lithium-supplementing negative electrode material.
[0023] In one embodiment of the present invention, the lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2.
[0024] In one embodiment of the present invention, the solvent in the polyurethane solution includes at least one of n-hexane, cyclohexane, ethyl acetate, toluene, xylene, tetrahydrofuran, N-methylpyrrolidone and N,N-dimethylformamide.
[0025] In one embodiment of the present invention, the concentration of the polyurethane solution is 2% to 20%.
[0026] In one embodiment of the present invention, the mass ratio of the lithium supplement agent to the polyurethane in the polyurethane solution is (95-99.5): (0.5-5).
[0027] In one embodiment of the present invention, the mixing process and the drying process are both performed under inert atmosphere conditions.
[0028] In one embodiment of the present invention, the inert atmosphere includes one of nitrogen, argon or helium.
[0029] In one embodiment of the present invention, the drying process is carried out at a temperature of 80° C. to 120° C. and for a time of 60 min to 240 min.
[0030] In one embodiment of the present invention, the mass ratio of the functional material to the silicon negative electrode particles is (5-15):(85-95).
[0031] In one embodiment of the present invention, the rotation speed of the ball milling treatment is 1000-6000 rpm, and the time is 10 min-240 min.
[0032] The present invention provides a negative electrode sheet, comprising the composite lithium-supplementing negative electrode material or the composite lithium-supplementing negative electrode material prepared by the above preparation method.
[0033] The present invention provides a secondary battery, comprising the negative electrode sheet.
[0034] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a composite lithium-supplementing negative electrode material, which uses a functional material with a core-shell structure to coat silicon negative electrode particles, which can inhibit the expansion of silicon negative electrode particles and improve the battery cycle performance to a certain extent. In addition, the functional material includes a lithium supplement core and a polyurethane material coating layer, which can play a lithium supplement effect; at the same time, during the battery charging process, lithium ions escape from the positive electrode and embed into the negative electrode, causing the negative electrode material to expand, and the particle expansion and extrusion will cause the polyurethane material in the functional material coating layer to rupture, releasing part of the lithium supplement, and realizing rapid lithium supplementation. When the battery is discharged, lithium ions escape from the negative electrode and embed into the positive electrode, and the negative electrode material shrinks. The repair function of polyurethane can be used to block the lithium supplement to avoid battery side reactions, thereby simultaneously improving the battery cycle performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram of the structure of the composite lithium-supplementing negative electrode material provided in this application;
[0036] Among them, 10 are silicon negative electrode particles; 20 are coating layers; 21 are lithium supplement agents; and 22 are polyurethanes. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0038] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0039] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0040] Regarding the problem of volume change of silicon negative electrode particles during the cycle, the existing technology can significantly reduce the volume expansion of the material during the cycle through methods such as nano-processing and surface coating, thereby improving the cycle performance of the battery. In addition, the existing technology also discloses pre-lithiation treatment of the material, and the use of lithium replenishers to replenish lithium to the positive and negative electrodes, so as to make up for the irreversible capacity loss of the battery during the first cycle of charging and discharging and the cycle process, and can also effectively improve the cycle life and storage performance of the lithium battery. However, the lithium replenishment method has extremely high requirements for environmental temperature and humidity, and highly active lithium metal or lithium replenishers are very easy to react with moisture in the air and carbon dioxide, etc., resulting in safety hazards to the battery and failure of the lithium replenisher.
[0041] The present invention provides a composite lithium-supplementing negative electrode material, which uses a functional material with a core-shell structure to coat silicon negative electrode particles, which can inhibit the expansion of silicon negative electrode particles and improve the battery cycle performance to a certain extent. In addition, the functional material includes a lithium supplement agent core and a polyurethane material coating layer, which can play a lithium supplement effect; at the same time, during the battery charging process, lithium ions escape from the positive electrode and embed into the negative electrode, causing the negative electrode material to expand, and the particle expansion and extrusion will cause the polyurethane material in the functional material coating layer to rupture, releasing part of the lithium supplement agent, and realizing rapid lithium supplementation. When the battery is discharged, lithium ions escape from the negative electrode and embed into the positive electrode, and the negative electrode material shrinks. The repair function of the polyurethane can be used to block the lithium supplement agent to avoid battery side reactions, thereby simultaneously improving the battery cycle performance and safety performance.
[0042] To achieve the above technical objectives, the technical solution of the present invention is as follows:
[0043] The present invention provides a composite lithium-supplementing negative electrode material (schematic structure as shown in Figure 1 As shown), it includes silicon negative electrode particles 10 and a coating layer 20 arranged on the surface of the silicon negative electrode particles, wherein the coating layer 20 includes a functional material; the functional material is a core-shell structure, the core 21 includes a lithium supplement, and the shell 22 includes a polyurethane material.
[0044] In an embodiment of the present invention, the silicon negative electrode particles include at least one of nano-silicon, silicon-oxygen material and silicon-carbon material.
[0045] In an embodiment of the present invention, the lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2.
[0046] In an embodiment of the present invention, the particle size D50 of the silicon negative electrode particles is 5 μm to 15 μm.
[0047] In an embodiment of the present invention, the coating layer has a thickness of 1 μm to 5 μm.
[0048] In an embodiment of the present invention, the particle size D50 of the lithium supplement agent is 0.2 μm to 0.8 μm.
[0049] In an embodiment of the present invention, the shell thickness of the polyurethane material is 2nm-50nm.
[0050] In an embodiment of the present invention, the mass ratio of the silicon negative electrode particles to the functional material is (85-95):(5-15).
[0051] In an embodiment of the present invention, the polyurethane material accounts for 0.5wt% to 5wt% of the coating layer.
[0052] In an embodiment of the present invention, the coating layer further includes carbon material.
[0053] In an embodiment of the present invention, the carbon material accounts for 20wt% to 40wt% of the coating layer. Too much or too little carbon material content will affect the initial efficiency, cycle performance and rate performance of the composite lithium supplement negative electrode material.
[0054] In an embodiment of the present invention, the carbon material includes one or more of graphene, carbon nanotubes and conductive carbon black.
[0055] The present invention also provides a method for preparing a composite silicon-carbon negative electrode sheet, comprising the following steps:
[0056] Mixing the lithium supplement agent and the polyurethane solution to obtain a mixed solution;
[0057] Drying the mixed solution to obtain a functional material;
[0058] The functional material and silicon negative electrode particles are ball-milled to obtain a composite lithium-supplementing negative electrode material.
[0059] In the step of mixing the lithium supplement agent and the polyurethane solution, after the lithium supplement agent and the polyurethane solution are mixed, the polyurethane solution and the lithium supplement agent are mixed evenly, so that the polyurethane solution can form a film layer on the surface of the lithium supplement agent, at least the polyurethane can be dispersed on the surface of the lithium supplement agent. Therefore, any mixing method that can make the lithium supplement agent and the polyurethane solution mix evenly is within the scope disclosed in the embodiment description of the present application, such as mixing methods such as but not limited to stirring or ball milling.
[0060] In an embodiment of the present invention, the lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2.
[0061] In an embodiment of the present invention, the solvent in the polyurethane solution includes at least one of n-hexane, cyclohexane, ethyl acetate, toluene, xylene, tetrahydrofuran, N-methylpyrrolidone and N,N-dimethylformamide.
[0062] In an embodiment of the present invention, the concentration of the polyurethane solution is 2% to 20%.
[0063] In an embodiment of the present invention, the mass ratio of the lithium supplement agent to the polyurethane in the polyurethane solution is (95-99.5):(0.5-5).
[0064] In an embodiment of the present invention, in the step of mixing the lithium supplement agent and the polyurethane solution, a carbon material is also added, the carbon material includes one or more of graphene, carbon nanotubes and conductive carbon black, and the mass ratio of the carbon material to the lithium supplement agent is (25-65): (95-99.5). Doping the carbon material in the coating layer on the surface of the silicon negative electrode particles can improve the conductivity of the composite lithium supplement negative electrode material, thereby improving the fast charging capability of the battery.
[0065] The step of drying the mixed solution is to remove the solvent contained in the mixed solution. Therefore, on the basis of ensuring the stability of the lithium supplement and the polyurethane, any drying method is within the scope disclosed in the embodiment of the present application, such as heating drying, reduced pressure drying or natural drying. Further, in the embodiment of the present invention, the drying temperature is 80°C to 120°C, and the time is 60min to 240min.
[0066] In an embodiment of the present invention, the mixing process and the drying process are both performed by continuously introducing a chemically inert gas. Specifically, the chemically inert gas can be a conventional chemically inert gas, such as at least one of argon, nitrogen, helium, and the like.
[0067] In an embodiment of the present invention, the mass ratio of the functional material to the silicon negative electrode particles is (5-15):(85-95).
[0068] In an embodiment of the present invention, the rotation speed of the ball milling treatment is 1000-6000 rpm, and the time is 10 min-240 min.
[0069] The present invention provides a negative electrode sheet, comprising the above-mentioned composite lithium-supplementing negative electrode material or the composite lithium-supplementing negative electrode material prepared by the above-mentioned preparation method. The negative electrode sheet of the embodiment of the present application comprises a negative electrode current collector and a negative electrode active layer bonded to the surface of the negative electrode current collector. Among them, the negative electrode active layer contains the composite lithium-supplementing negative electrode material of the above-mentioned embodiment of the present application. Since the negative electrode sheet of the embodiment of the present application contains the above-mentioned composite lithium-supplementing negative electrode material of the embodiment of the present application, during the charging and discharging process, the composite lithium-supplementing negative electrode material contained in the negative electrode sheet plays the above-mentioned role, which can not only inhibit the expansion of silicon negative electrode particles, but also improve the battery cycle performance; at the same time, during the battery charging process, lithium ions are removed from the positive electrode and embedded in the negative electrode, causing the negative electrode material to expand, and the polyurethane material in the functional material coating layer is broken, releasing part of the lithium supplement agent, and realizing rapid lithium supplementation. When the battery is discharged, lithium ions are removed from the negative electrode and embedded in the positive electrode, and the negative electrode material shrinks, the lithium supplement agent can be blocked by the repair function of the polyurethane to avoid battery side reactions, thereby simultaneously improving the battery cycle performance and safety performance.
[0070] In an embodiment of the present invention, the negative electrode active layer further comprises a binder and a conductive agent, wherein the binder may be a commonly used electrode binder, such as one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives. In an embodiment of the present application, the conductive agent may be a commonly used conductive agent, such as one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes.
[0071] In an embodiment of the present invention, the negative electrode sheet preparation process can be: mixing the above-mentioned composite lithium-supplementing negative electrode material, conductive agent and binder to obtain electrode slurry, coating the negative electrode slurry on the negative electrode collector, and preparing the negative electrode sheet through drying, rolling, die cutting and other steps.
[0072] The present invention provides a secondary battery, comprising the negative electrode sheet.
[0073] In one embodiment of the present invention, the secondary battery further comprises a positive electrode sheet, a separator and an electrolyte. In the present application, the composition ratio and preparation method of the positive electrode sheet, the separator and the electrolyte are not limited and conventional operations in the art may be used.
[0074] Specifically, the positive electrode active material in the positive electrode sheet may include at least one of lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium iron phosphate, lithium iron manganese fluorophosphate, and lithium nickel iron manganese oxide; the material of the diaphragm may include at least one of polyethylene, polypropylene, polyacrylonitrile, polyvinyl alcohol, polyarylether sulfone, and polyvinylidene fluoride; the solvent in the electrolyte may include a carbonate solvent and / or an ether solvent, and the lithium salt in the electrolyte may include at least one of LiPF6, LiBF4, LiTFSI, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2.
[0075] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0076] Example 1
[0077] This embodiment provides a method for preparing a composite lithium-supplementing negative electrode material:
[0078] In a glove box, lithium metal powder of a lithium supplement agent and polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent) are mixed in a mass ratio of 95:5 to obtain a mixed solution;
[0079] Under an inert atmosphere containing argon, the mixed solution is dried at 80° C. for 100 minutes to obtain a functional material;
[0080] The functional material and silicon negative electrode particles (silicon-carbon negative electrode material) with a mass ratio of 5:95 were ball-milled at a rotation speed of 4500 rpm for 30 minutes to obtain a composite lithium-supplementing negative electrode material.
[0081] Example 2
[0082] This embodiment provides a method for preparing a composite lithium-supplementing negative electrode material:
[0083] In a glove box, lithium metal powder of a lithium supplement agent and polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent) are mixed in a mass ratio of 99.5:0.5 to obtain a mixed solution;
[0084] Under an inert atmosphere containing argon, the mixed solution is dried at 80° C. for 100 minutes to obtain a functional material;
[0085] The functional material and silicon negative electrode particles (silicon-carbon negative electrode material) with a mass ratio of 5:95 were ball-milled at a rotation speed of 4500 rpm for 30 minutes to obtain a composite lithium-supplementing negative electrode material.
[0086] Example 3
[0087] This embodiment provides a method for preparing a composite lithium-supplementing negative electrode material:
[0088] In a glove box, lithium metal powder of a lithium supplement agent and polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent) are mixed in a mass ratio of 97:3 to obtain a mixed solution;
[0089] Under an inert atmosphere containing argon, the mixed solution is dried at 80° C. for 100 minutes to obtain a functional material;
[0090] The functional material and silicon negative electrode particles (silicon-carbon negative electrode material) with a mass ratio of 5:95 were ball-milled at a rotation speed of 4500 rpm for 30 minutes to obtain a composite lithium-supplementing negative electrode material.
[0091] Example 4
[0092] This embodiment provides a method for preparing a composite lithium-supplementing negative electrode material:
[0093] In a glove box, lithium metal powder of a lithium supplement agent and polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent) are mixed in a mass ratio of 95:5 to obtain a mixed solution;
[0094] Under an inert atmosphere containing argon, the mixed solution is dried at 80° C. for 100 minutes to obtain a functional material;
[0095] The functional material and silicon negative electrode particles (silicon-carbon negative electrode material) with a mass ratio of 15:85 were ball-milled at a rotation speed of 4500 rpm for 30 minutes to obtain a composite lithium-supplementing negative electrode material.
[0096] Example 5
[0097] This embodiment provides a method for preparing a composite lithium-supplementing negative electrode material:
[0098] In a glove box, lithium metal powder of a lithium supplement agent and polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent) are mixed in a mass ratio of 95:5 to obtain a mixed solution;
[0099] Under an inert atmosphere containing argon, the mixed solution is dried at 80° C. for 100 minutes to obtain a functional material;
[0100] The functional material and silicon negative electrode particles (silicon-carbon negative electrode material) with a mass ratio of 10:90 were ball-milled at a rotation speed of 4500 rpm for 30 minutes to obtain a composite lithium-supplementing negative electrode material.
[0101] Example 6
[0102] This embodiment provides a method for preparing a composite lithium-supplementing negative electrode material:
[0103] In a glove box, lithium metal powder of a lithium supplement agent and polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent) are mixed in a mass ratio of 95:5 to obtain a mixed solution;
[0104] Under an inert atmosphere containing argon, the mixed solution is dried at 100° C. for 60 minutes to obtain a functional material;
[0105] The functional material and silicon negative electrode particles (silicon-carbon negative electrode material) with a mass ratio of 5:95 were ball-milled at a rotation speed of 4500 rpm for 30 minutes to obtain a composite lithium-supplementing negative electrode material.
[0106] Example 7
[0107] This embodiment provides a method for preparing a composite lithium-supplementing negative electrode material:
[0108] In a glove box, lithium metal powder of a lithium supplement agent and polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent) are mixed in a mass ratio of 95:5 to obtain a mixed solution;
[0109] Under an inert atmosphere containing argon, the mixed solution is dried at 80° C. for 100 minutes to obtain a functional material;
[0110] The functional material and silicon negative electrode particles (silicon-carbon negative electrode material) with a mass ratio of 5:95 were ball-milled at a rotation speed of 4800 rpm for 25 minutes to obtain a composite lithium-supplementing negative electrode material.
[0111] Example 8
[0112] This embodiment provides a method for preparing a composite lithium-supplementing negative electrode material:
[0113] In a glove box, lithium metal powder of a lithium supplement agent, polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent, etc.) and carbon material (carbon nanotubes) are mixed in a mass ratio of 95:5:65 to obtain a mixed solution;
[0114] Under an inert atmosphere containing argon, the mixed solution is dried at 80° C. for 100 minutes to obtain a functional material;
[0115] The functional material and silicon negative electrode particles (silicon-carbon negative electrode material) with a mass ratio of 5:95 were ball-milled at a rotation speed of 4500 rpm for 30 minutes to obtain a composite lithium-supplementing negative electrode material.
[0116] Example 9
[0117] This embodiment provides a method for preparing a composite lithium-supplementing negative electrode material:
[0118] In a glove box, lithium metal powder of a lithium supplement agent, polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent) and carbon material (carbon nanotubes) are mixed in a mass ratio of 95:5:25 to obtain a mixed solution;
[0119] Under an inert atmosphere containing argon, the mixed solution is dried at 80° C. for 100 minutes to obtain a functional material;
[0120] The functional material and silicon negative electrode particles (silicon-carbon negative electrode material) with a mass ratio of 5:95 were ball-milled at a rotation speed of 4500 rpm for 30 minutes to obtain a composite lithium-supplementing negative electrode material.
[0121] Comparative Example 1
[0122] This comparative example provides a method for preparing a composite negative electrode material:
[0123] In a glove box, lithium metal powder of a lithium supplement agent and polyurethane (polyurethane solution concentration is 15%, the solvent is tetrahydrofuran, the polyurethane is first dissolved in the solvent and then mixed with the lithium supplement agent) are mixed in a mass ratio of 95:5 to obtain a mixed solution;
[0124] The mixed solution was dried at 80° C. for 100 min under an inert atmosphere containing argon to obtain a composite negative electrode material.
[0125] Comparative Example 2
[0126] This comparative example provides a commercially available silicon-carbon negative electrode material.
[0127] Preparation of lithium-ion batteries:
[0128] The negative electrode sheet, separator, and positive electrode sheet of nickel cobalt manganese oxide prepared in the above-mentioned Examples 1 to 9 and Comparative Examples 1 to 2 are wound to obtain a battery cell, and the battery cell is placed in a battery shell, dried, electrolyte injected, packaged, formed, and volume divided to obtain a lithium-ion battery. Among them, the positive electrode sheet is: lithium nickel cobalt manganese oxide is mixed with a conductive agent (conductive carbon black and carbon nanotubes are mixed in a mass ratio of 19:1) and a PVDF adhesive material in a mass ratio of 97.5:1.5:1, mixed with NMP as a solvent and then coated on an aluminum foil, and dried, rolled, cut, and striped to obtain a positive electrode sheet; the separator is a polyethylene separator; the electrolyte is prepared by dissolving LiPF6 in a solvent EC&DMC (volume ratio 1:1), and the LiPF6 concentration is 1M.
[0129] Electrical performance test: The lithium ion batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were subjected to energy density tests, and the battery's first coulombic efficiency and cycle performance (number of cycles corresponding to a capacity decay of 80%) were tested under a temperature of 25°C, a charge and discharge rate of 0.3C / 0.3C and a charge and discharge rate of 1C / 1C, and a charge and discharge voltage range of 2.75V to 4.25V. The test results are shown in Table 1.
[0130] The electrical performance test results of the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 4 are shown in Table 1.
[0131] Table 1 Electrical performance test results of Examples 1 to 7 and Comparative Examples 1 to 4
[0132]
[0133]
[0134] From the results in Table 1, it can be seen that the lithium-ion battery prepared by the composite lithium-replenishing negative electrode material prepared by the method of the present invention has greatly improved first coulombic efficiency, cycle performance and rate performance compared with the lithium-ion battery prepared by the polymer-coated silicon-carbon negative electrode material (Comparative Example 1) and the conventional silicon-carbon negative electrode material (Comparative Example 2). This is because the composite lithium-replenishing negative electrode material prepared in this application can both inhibit the expansion of silicon negative electrode particles and improve the battery cycle performance; at the same time, during the battery charging process, the polyurethane material in the functional material coating layer breaks, releasing part of the lithium-replenishing agent to achieve rapid lithium replenishment. During the battery discharge process, the repair function of the polyurethane can block the lithium-replenishing agent to avoid battery side reactions, thereby simultaneously improving the battery cycle performance and safety performance. From the comparison of Example 1 and Examples 8 and 9, it can be seen that when the surface of the silicon negative electrode particles contains carbon material, the fast charging performance of the material can also be improved to a certain extent. This is because the carbon material can improve the conductivity of the composite lithium-replenishing negative electrode material and reduce the internal resistance of the material.
[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite lithium-supplementing negative electrode material, characterized in that: The composite lithium-supplementing negative electrode material comprises silicon negative electrode particles and a coating layer arranged on the surface of the silicon negative electrode particles, wherein the coating layer comprises a functional material; the functional material is a core-shell structure, wherein the core comprises a lithium-supplementing agent and the shell comprises a polyurethane material.
2. The composite lithium-supplementing negative electrode material according to claim 1, characterized in that: The silicon negative electrode particles include at least one of nano-silicon, silicon-oxygen materials and silicon-carbon materials; the lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2 and Li2CuO2.
3. The composite lithium-supplementing negative electrode material according to claim 1, characterized in that: The particle size D50 of the silicon negative electrode particles is 5 μm to 15 μm, and the thickness of the coating layer is 1 μm to 5 μm; the particle size D50 of the lithium supplement agent is 0.2 μm to 0.8 μm, and the shell thickness of the polyurethane material is 2 nm to 50 nm.
4. The composite lithium-supplementing negative electrode material according to claim 1, characterized in that: The mass ratio of the silicon negative electrode particles to the functional material is (85-95):(5-15); the polyurethane material accounts for 0.5wt%-5wt% of the coating layer.
5. The composite silicon-carbon negative electrode sheet according to claim 1, characterized in that: The coating layer further comprises a carbon material, which accounts for 20 wt% to 40 wt% of the coating layer. The carbon material comprises one or more of graphene, carbon nanotubes and conductive carbon black.
6. A method for preparing a composite lithium-supplementing negative electrode material, characterized in that: The following steps are involved: The lithium supplement agent and the polyurethane solution are mixed to obtain a mixed solution; Drying the mixed solution to obtain a functional material; The functional material and silicon negative electrode particles are ball-milled to obtain a composite lithium-supplementing negative electrode material.
7. The preparation method according to claim 6, characterized in that: In the step of mixing the lithium supplement agent and the polyurethane solution, at least one of the following characteristics is met: (1) The lithium supplement includes at least one of metallic lithium, lithium carbonate, lithium hydroxide, lithium oxide, lithium nitride, Li5FeO4, Li6CoO4, Li2NiO2, and Li2CuO2; (2) The solvent in the polyurethane solution includes at least one of n-hexane, cyclohexane, ethyl acetate, toluene, xylene, tetrahydrofuran, N-methylpyrrolidone and N,N-dimethylformamide; (3) The concentration of the polyurethane solution is 2% to 20%; (4) The mass ratio of the lithium supplement agent to the polyurethane in the polyurethane solution is (95-99.5): (0.5-5).
8. The preparation method according to claim 6, characterized in that: The drying process is performed at a temperature of 80° C. to 120° C. and for a time of 60 min to 240 min.
9. The preparation method according to claim 6, characterized in that: The mass ratio of the functional material to the silicon negative electrode particles is (5-15): (85-95); and / or the rotation speed of the ball milling treatment is 1000-6000 rpm, and the time is 10 min-240 min.
10. A negative electrode sheet, characterized in that: The invention comprises the composite lithium-supplementing negative electrode material according to any one of claims 1 to 5 or the composite lithium-supplementing negative electrode material prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Elastomer-encapsulated particles of high-capacity anode active materials for lithium batteries
CN108886143A
Long-life quick-charge type lithium ion battery negative electrode material and preparation method thereof
CN114613974A
Preparation method of negative electrode material for energy storage lithium ion battery
CN116470032A
Battery and preparation method thereof
CN116487529A
Modified lithium supplement agent and modification method and application thereof
CN117790941A
Cited By
Composite lithium supplement additive and preparation method and application thereof
CN120048890A